SINERGITAS PENGEMBANGAN KURIKULUM PAI DALAM PENDIDIKAN - Khoirotun Nisak (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2019)
Islamic education curriculum has central value for education process, as education vision direction. Islamic education mission is how to create religious people by leaning perfectly. Curriculum becomes one of success applications and quality in education institution most. Curriculum will develop based on global world and people life style existency. Therefore, education should view people life style increased as learning source that is becomed a value for curriculum step making. Beside that, islamic education curriculum development also becomes teacher’s choice to implement learning manner in class. In where, it’s implementation should be arranged and systematically to make maximal learning either in development vision, indicator, lesson teory, lesson model proccess, learning evaluation or teacher’s development skill. The process of islamic education curriculum development must be done good and awesome also seeing several factors as supports and obstacles of it. In other to get an education result based on such the plan made before(education planning).